Labour market reforms in Italy: Evaluating the efects of the Jobs Act - Marta Fana; Dario Guarascio; Valeria Cirillo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2015)
Law 183 of 2014, evocatively named the "Jobs Act", has determined a deep change in the Italian industrial relations. Bringing at completion a reform process begun in the 1990s, the Jobs Act has introduced a new contract type - "contratto a tutele crescenti" - implying a substantial downsize of obligation for workers' reinstatement in case of firms invalidly firing them. The new permanent contract is therefore deprived of the substantial requirements of an open-ended contract. The Law has also weakened the legal constraints for firms intending to monitor workers through electronic devices and introduced new incentives for firms using temporary contracts. This article frames the Jobs Act within the overall labour market reform process occurred in Italy since mid-nineties and provides a first evaluation of its impacts on the Italian labour market. Taking advantage of different data sources (administrative and labour force data) and concentrating the analysis over the period after the Jobs Act implementation, the investigation provides the following results: the expected boost in employment growth is not detected; an increase in the share of temporary contracts over the open-ended ones is observed; a raise of part-time contracts within the new permanent positions emerges. The analysis shows that the Jobs Act failed in achieving its main goals. We discuss the observed evidence evaluating the appropriateness of the Law 183/2014 in the present Italian economic context accounting, in particular, for the structural effects of the recent crisis.
Keywords: 330